2D MOF induced accessible and exclusive Co single sites for an efficient O-silylation of alcohols with silanes. Issue 46 (21st May 2019) - Wang, Xin; Li, Peng; Li, Zhijun; Chen, Wenxing; Zhou, Huang; Zhao, Yafei; Wang, Xiaoqian; Zheng, Lirong; Dong, Juncai; Lin, Yue; Zheng, Xusheng; Yan, Wensheng; et al.
Abstract : Cobalt single sites on ultrathin two-dimensional nitrogen doped carbon (Co SAs/2D N–C) derived from 2D metal–organic frameworks (MOF). Abstract : Co single atoms anchored on ultrathin two-dimensional nitrogen-doped carbon (Co SAs/2D N–C) were in situ derived from 2D metal–organic frameworks (MOFs). These ultrathin nanosheets functionalized by the isolated Co atoms possess a high density of active sites and accessible surfaces, exhibiting an exceptional catalytic performance in the oxidation of silanes.